Freedom as a Polyphonic Concept in the "vota" for the Second Vatican Council - Wąsek, Damian (Verbum vitae, 2025)
This article explores the multifaceted nature of freedom that emerges from the various vota sent from around the world in the antepreparatory phase of the Second Vatican Council. The voices of bishops and institutions, each with their unique perspective, are structured into five categories. The first is the foundations and sources of freedom often presented in a polemical aspect. The second category is the issue of free will and freedom of conscience. The third concerns freedom within the Catholic Church. The fourth issue considered is freedom in ecumenical and interreligious dialogue. The last reflection explores freedom in the area of state governance and its relationship with the Church. The whole is concluded by detailing the tensions in the positions cited above, with a commentary that demonstrates the topicality of the issue addressed.